PET/CT in Colorectal Cancer - Du, Yong (Springer International Publishing : Imprint: Springer, 2017)
This book is a pocket guide to the science and practice of PET/CT imaging of colorectal malignancies. The role of PET/CT in these patients, the characteristic PET/CT findings, and the advantages and limitations of this hybrid modality are all clearly described. In addition, information is provided on clinical presentation, diagnosis, staging, pathology, management, and radiological imaging. The book is published within the Springer series Clinicians' Guides to Radionuclide Hybrid Imaging, which is aimed at nuclear medicine/radiology residents and physicians, referring clinicians, radiographers/technologists, and nurses who routinely work in nuclear medicine and participate in multidisciplinary meetings. Compiled under the auspices of the British Nuclear Medicine Society, the series is the joint work of many colleagues and professionals worldwide who share a common vision and purpose in promoting and supporting nuclear medicine as an important imaging specialty for the diagnosis and management of oncological and non-oncological conditions.
Keywords: Medicine.; Nuclear medicine.; Oncology.; elektronické knihy; electronic books